Does Emotional Intelligence Prompt Knowledge Sharing Behavior among Academic Staff - Hatamleh, Dr. Amer (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The presented paper aims to reveal the direct and indirect relationship between emotional intelligence and knowledge sharing behavior among academic staff in Jordanian universities. Furthermore, it aims to examine the mediation effect of knowledge sharing intention on the relationship between emotional intelligence and knowledge sharing behavior. Convenience sampling was used to collect data from 191 academic staff from private universities in the northern region of Jordan. First, data were tested for validity and reliability. Second, Structural Equation Modeling (SEM) was applied to analyze the model and hypothesis testing. The results indicated that emotional intelligence has a direct and indirect relationship with academic staff knowledge sharing behavior. Furthermore, the results indicated that knowledge sharing intention partially mediates the relationship between emotional intelligence and academic staff knowledge sharing behavior. The limitations of this study include the sampling and cross-sectional design. Hence, future studies can be conducted using a longitudinal design covering other public universities to increase the generalizability of findings. The findings suggest that top management in universities should develop appropriate strategies for improving the emotional intelligence level of academic staff because academic staffs with higher emotional intelligence are more likely to engage themselves in knowledge sharing activities. Furthermore, universities should conduct various training and education programs to improve the level of emotional intelligence among academic staff, thereby fostering knowledge sharing in universities. Furthermore, there is limited literature on the role of emotional intelligence in knowledge sharing behavior among academic staff. The study adds to the extant literature on emotional intelligence and both knowledge sharing intention and knowledge sharing behavior in the context of universities. Besides, the study attempted to investigate the direct and indirect effect of emotional intelligence on knowledge sharing behavior that has not been studied so far.